A numerical simulation method of nonlinear magnetic flux leakage testing signals for nondestructive evaluation of plastic deformation in a ferromagnetic material. (16th June 2021) - He, Manru; Shi, Pengpeng; Xie, Shejuan; Chen, Zhenmao; Uchimoto, Tetsuya; Takagi, Toshiyuki
Abstract: Nonlinear Magnetic Flux Leakage Testing (MFLT) method is a relative new non-destructive testing (NDT) technique for inspection defect or micro damage in structure of ferromagnetic material by measuring the leakage magnetic field during an alternative magnetization process. To enhance the nonlinear MFLT technique, a numerical tool for simulating the inspection signal is very important in views to clarify the detection mechanism and to improve the detection efficiency. However, most of the simulation methods on magnetic NDT problems solve problem without considering the hysteresis effects of ferromagnetic materials and is difficult to deal with the influence of mechanical damage. In this paper, a numerical scheme is proposed at first to simulate the nonlinear MFLT signals considering the nonlinearity and hysteresis characteristics of ferromagnetic materials based on the equivalent magnetic polarization approach and FEM-BEM hybrid method. The validities of the proposed method and the corresponding numerical code are proved by comparing the simulation results of a typical nonlinear MFLT problem with the experimental measured signals. Secondly, in order to cope with the influence of plastic deformation in material on the nonlinear MFLT signals, a magneto-mechanical coupling constitutive relation is proposed and applied to the developed numerical simulation code. Finally, the nonlinear MFLT signals of specimen with different plastic deformation are simulated with the developed numerical code and the influence mechanism of plastic deformation on nonlinear MFLT signals is discussed based on the numerical results. The results reveal that the distortion of nonlinear MFLT signals mainly due to the magnetic remanence coefficient of material which can be significantly influenced by micro damage such as the plastic deformation.